Gwarancje bankowe w obrocie gospodarczym - Gubernat, Ewa (Banking Guarantees in Economic Transactions, 2008)
Risk is one of the most important elements of economic activity. Every economic undertaking can be completed with success or more or less important breakdown. The global economy does not minimize risk of economic activity but it disperses risk. So for this reason and to minimize this kind of risk, banking guarantees are becoming more and more popular. Thanks to this solution, it is possible to successfully control risk.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 79-88